Improvement of the Signalized Intersection - Harun, Muhamad Taufiq (IRC, 2019)
Improvement of the signalized intersections is essential for the traffic users. By doing this research, the author can analyse and interpret the data taken from the field of study by using the SIDRA Intersection software version 5.1. This studies will highlighted the Level of Services at the designated location which is in front of UTP and at the Bandar Universiti Intersections during the peak hour by one week. The data taken is analysed then the optimum setting for signalized intersection is proposed based on the results in order to enhance and increase the improvement of the designated intersections. The analysis and output given by the software is the objective from this final year project at the study area.